TEACHING ESP USING MYKLASS IN UNIVERSITAS MUHAMMADIYAH YOGYAKARTA: STUDENTS’ PERCEPTION - Farahsani, Yashinta; Harmanto, Margaretha Dharmayanti (LLT Journal: A Journal on Language and Language Teaching, 2022)
Many non-English departments study English for Specific Purposes (ESP) to improve students' vocabulary related to their field. UMY has established a program called MyKlass as a facility to do online learning. This program provides many features, such as sharing materials in the form of documents, pictures, or media; conducting quizzes; assignment submission; and attendance. However, teaching ESP using MyKlass also faces some difficulties such as students' motivation to read the material, the teacher's control in evaluating students' study progress, and students' problem in improving English vocabulary in specialized language. Using a questionnaire distributed to 234 Accounting and Mechanical Engineering students, the writers found out the students' perception of using MyKlass from their motivation and perception in learning ESP using MyKlass, their perception of the aspects of benefits, and their perception of learning ESP Using MyKlass. Most of the answers showed positive responses; therefore, we can conclude that ESP online learning using MyKlass has been very beneficial to the students regardless of the technical problems that students sometimes encounter.